Heracleum piliferum (Apiaceae), a new species from central Nepal - Kljuykov, Eugene; Lyskov, Dmitry; Ukrainskaja, Uliana; Samigullin, Tahir; Terentieva, Elena (Phytotaxa, 2021)
A new species, Heracleum piliferum (Apiaceae), is described from the Annapurna mountain massif, central Nepal. The new species is related to H. forrestii and H. hemsleyanum and differs from them in dense pubescence of petioles, short triangular sheaths of stem leaves, 2-pinnate leaf blades, shallow notched terminal leaf segments, crenulate leaf margin, larger terminal umbels, and broadly winged lateral ribs of the mericarps.